PERSEPSI MASYARAKAT AKAN PENTINGNYA SOCIAL DISTANCING DALAM PENANGANAN WABAH COVID-19 DI INDONESIA - Nina Novira; Rudi Iskandar; Raehanul Bahraen (Jurnal Kependudukan Indonesia, 2020)
COVID-19 has spread worldwide including Indonesia. The government responds by appealing to the public toimplement social distancing (sd) to contained the spread of the virus. However, without threats Concrete penalties andthe absence of strict safeguards make the application of SD dependent on perception and compliance community only. Seeing the fact that some people continue their activities outside the home, various assumptions developing in thecommunity. By using Google Form Â®, this study aims to analyze perceptions the public on the importance ofimplementing SD as an effort to deal with Covid-19, confirmed the general assumptions that develops in thecommunity, and traces the causes of the ineffectiveness of elementary school application. Research result shows thatmost of the community believes that adoption of SD is very important. However, that perception not always directlyproportional to the appropriate behavior. The general perception is that those who stay out of the house are in thecontext of work and earning a living is not proven. Compared to attending invitations and stays organizing events thathave been planned since before the plague, still worship in more houses of worship many cause people to leave thehouse